2022
DOI: 10.4209/aaqr.220183
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Applications to Dust Storms: A Meta-Analysis

Abstract: Dust storms are natural hazards that affect both people and properties. Therefore, it is important to mitigate their risks by implementing an early notification system. Different methods are used to predict dust storms, such as observing satellite images, analyzing meteorological data, and using numerical weather prediction model forecasts. However, recent studies have shown that machine learning algorithms have higher capacities to predict dust storms in less time and with fewer processing operations compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To address this challenging task, several studies have been tried in the past. These approaches can broadly be categorized as the use of artificial intelligence/machine learning (AI/ML) (40,41), physical factors and modelling techniques (42,43), remote sensing, statistical predictive models, and game theory (44), or the Air Quality Early Warning System (45). After thorough examination (41), it was concluded that the application of AI/ML approach has various inherent constraints, including quantity and quality of the training dataset along with the complexity of the processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this challenging task, several studies have been tried in the past. These approaches can broadly be categorized as the use of artificial intelligence/machine learning (AI/ML) (40,41), physical factors and modelling techniques (42,43), remote sensing, statistical predictive models, and game theory (44), or the Air Quality Early Warning System (45). After thorough examination (41), it was concluded that the application of AI/ML approach has various inherent constraints, including quantity and quality of the training dataset along with the complexity of the processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, major benefit of the HDWI approach lies in its computational efficiency, which stands in stark contrast to the computationally demanding and resource-intensive AI/ML approach, remote sensing, statistical predictive models, game theory, or the Air Quality Early Warning System. The HDWI method exclusively utilizes physical factors, rather than depending on statistical approaches and/or pattern identification (41). Another advantage of HDWI method is its capacity to function independently, and requiring less dependency on external resources.…”
Section: Introductionmentioning
confidence: 99%